A reliability evaluation method of complex electromechanical products based on the multi-stress coupling acceleration model. (April 2023) - Pan, Guangze; Ding, Xiaojian; Li, Dan; Li, Yaqiu; Wang, Yuanhang
Highlights: Establishing a coupling competition physical of failure model based on Copula function. Putting forward a multi-stress coupling quantitative method based on coupling matrix. Proposing a reliability evaluation method that considers multi-stress coupling acceleration and coupling competitive failure. The method proposed is more accurate and more applicable than the traditional methods. Abstract: This paper proposes a reliability evaluation method based on a multi-stress coupling acceleration model. It can be used for testing complex electromechanical products that have high reliability, long lifetimes and small samples. Considering complex and diverse failure modes, as well as the coupled competitive characteristics of electromechanical products, a coupling competition physics of failure (PoF) model based on a Copula function was constructed, together with a proposed solution. Regarding the complex stress types and coupling relations that occur during the service of electromechanical products, a multi-stress coupling quantitative method based on a coupling matrix is proposed to analyse multi-stress coupling failure mechanisms. Moreover, the developed model is a multi-stress coupling acceleration model, which is solved using a maximum-likelihood function and covariance matrix. Finally, the reliability of a servo system was evaluated and the results compared with those of a traditional method without consideration of coupling competition of failure modes and multi-stress coupling. The proposed method is superior in terms of evaluation accuracy and application range.